Evaluation of the ventilation situation in Dutch schools using the QuickScan method - Krishnan, Vinayak; Loomans, Marcel; Walker, Shalika; Zeiler, Wim (CLIMA 2022 conference, 2022)
The COVID19 pandemic has brought especially the health aspect to the forefront and the need to improve ventilation in Dutch schools. To assess the ventilation in schools during the pandemic, the QuickScan method was developed by a large National consortium called ‘Masterplan Ventilatie’. The method contains a list of instructions for users to quickly evaluate the quality of ventilation. As part of this study, 25 TU Eindhoven bachelor students were provided with the QuickScan documentation and children and teacher questionnaires were added to assess the ventilation systems, each in a different Dutch school. These results have been used to identify the possibilities and limitations of the QuickScan method and provide information on the current ventilation status in the investigated schools. Firstly, administrative (i.e., information gathering and reporting) and functional (i.e., measurements and data analysis) groups of steps are distinguished. Secondly, scoring criteria are defined to rate each individual step of the QuickScan performed by the students. The questionnaires pointed at uncomfortable winter conditions, limited possibilities for ventilation control, poor air quality, and inadequate cleanliness for schools. The measurements show that 50% of the schools, which indicated maximum CO2 levels during occupancy, recorded levels above 1200 ppm. About 67% of the studies, which reported the ventilation capacity for the worst or winter operating conditions, recorded insufficient ventilation. The balanced mechanical ventilation system rated better based on the teacher questionnaires while the children questionnaires indicated no preference for a specific ventilation system. The QuickScan evaluation highlighted that 100% of the studies achieved at least 60% completion for the administrative steps and only 52% of the studies achieved at least 60% completion for the functional steps. This study is the first to apply the QuickScan method, report results, and provide an approach to evaluate and suggest improvements to the QuickScan method.